IFRS adoption and financial reporting quality in the telecommunication industry:a case study of mtn Uganda - Trisha Mbabazi (Uganda Christian University, 2026)
This study explored how the adoption of International Financial Reporting Standards (IFRS) changed the quality of financial reports in Uganda’s telecommunications sector, with MTN Uganda as a detailed case. The research closely focused on three major standards IFRS 15, IFRS 9, and IFRS 16. Using a mix of survey responses from key stakeholders’ investors, financial analysts, and accountants along with a review of MTN’s annual reports before and after IFRS adoption, it emerged that stakeholders largely agreed that financial reporting at MTN Uganda has improved since IFRS was introduced. Reports are seen as more detailed, easier to compare with regional peers such as Airtel, and more trustworthy especially when it comes to recognizing revenue and accounting for leases and credit risks. However, the study also revealed significant hurdles. Many respondents noted that the new reports, while more thorough, have also become harder to understand. Others pointed to the difficulty of making reliable financial estimates in Uganda’s unpredictable economy, as well as the high costs of implementing these complex standards. These challenges remind us that global accounting rules may not always translate smoothly into local contexts. In the end, this research affirms that IFRS adoption has strengthened financial reporting at MTN Uganda. This has further brought it closer to global benchmarks and boosted confidence among investors and regulators. But the journey is not complete. To make the most of these standards, Uganda’s telecom sector will need more guidance, training, and perhaps even tailored interpretations of IFRS to match local realities.
Undergraduate